Family history of liver cancer may modify the association between HBV infection and liver cancer in a Chinese population. (10th July 2019) - Liu, Xing; Baecker, Aileen; Wu, Ming; Zhou, Jin‐Yi; Yang, Jie; Han, Ren‐Qiang; Wang, Pei‐Hua; Jin, Zi‐Yi; Liu, Ai‐Min; Gu, Xiaoping; Zhang, Xiao‐Feng; Wang, Xu‐Shan; et al.
Abstract: Background & Aims: The potential interaction between family history of liver cancer and HBV infection on liver cancer has not been fully examined. Methods: We conducted a population‐based case‐control study composed of 2011 liver cancer cases and 7933 controls in Jiangsu province, China from 2003 to 2010. Data on major risk or protective factors were collected and HBV/HCV sero‐markers were assayed using blood samples. Semi‐Bayes (SB) adjustments were applied to provide posterior estimates. Results: Both family history of liver cancer (adjusted odds ratios [OR]: 4.32, 95% confidence intervals [CI]: 3.25‐5.73) and hepatitis B surface antigen (HBsAg) positivity (adjusted OR: 9.94, 95% CI: 8.33‐11.87) were strongly associated with liver cancer development. For individuals with different combinations of serological markers, the adjusted ORs were 8.45 (95% CI: 5.16‐13.82) for HBsAg‐ and HBcAb‐positive; 7.57 (95% CI: 4.87‐11.77) for HBsAg‐, HBeAg‐ and HBcAb‐positive; and 3.62 (95% CI: 2.47‐5.31) for HBsAg‐, HBeAb‐ and HBcAb‐positive, compared to all negatives in HBV serological markers. One log increase in HBV DNA level was associated with 17% increased risk (adjusted OR: 1.17, 95% CI: 1.03‐1.32). The SB‐adjusted OR of HBV‐positive individuals with family history of liver cancer was 41.34 (95% posterior interval [PI]: 23.69‐72.12) compared with those HBV‐negative without family history. Relative excess risk due to additive interaction, the attributable proportion and synergy index were 73.13, 0.87 and 8.04 respectively. Adjusted ratio of OR for multiplicative interaction was 2.84 (95% CI: 1.41‐5.75). Conclusions: Super‐additive and super‐multiplicative interactions may exist between family history of liver cancer and HBV infection on the development of liver cancer.